Hubungan Pengetahuan dengan Kecukupan Gizi Mahasiswa Pendidikan Kesejahteraan Keluarga Konsentrasi Tata Boga - Fadillah, Mayang; Yulastri, Asmar; Fridayati, Lucy (Journal of Home Economics and Tourism, 2016)
This study aimed to describe the nutritional knowledge, nutritional adequacy and analyzing their relationship with the knowledge of nutritional adequacy. This study is correlational with a population of 182 people and a sample of 28 people who is taken amid proportional random sampling technique. Data collection techniques for knowledge of nutrition using a questionnaire enclosed in the form of multiple choice, while for nutritional adequacy using open questionnaire form of food recall. The results showed that the nutrition knowledge of students included into the category is as high as (25%) and (17.8%) students have the knowledge of the high category. In the variable nutritional adequacy indicates that the highest energy intake of students (3999.4kcal) and the lowest intake of (421.2kcal). Correlation test results showed that the correlation is positive and significant correlation between knowledge with nutritional adequacy with thitung 6,961 students at the significance level of 0.000. Contributions knowledge of nutrition on the nutritional adequacy of students amounted to 24.1%Keyword: Nutrition Knowledge, Nutritional Adequacy